Essays on how health and education affect the labor market outcomes of workers - Namingit, Sheryll (Kansas State University, 2017)
This dissertation consists of three essays on how health and education affect the labor market outcomes of workers. Health and education issues have been key determinants of labor demand and supply. In light of increasing incidence of health problems and the rapid growth of post-baccalaureate certificates in the US, this dissertation seeks to answer questions about labor market outcomes of workers with poor health history and with post-baccalaureate certificates. The first essay which I co-authored with Dr. William Blankenau and Dr. Benjamin Schwab uses a résumé-based correspondence test to compare the employment consequences of an illness-related employment gap to those of an unexplained employment gap. The results of the experiment show that while the callback rate of applicants with an illness-related employment gap is lower than that of the newly unemployed, applicants with illness-related employment gaps are 2.3 percentage points more likely to receive a callback than identical applicants who provide no explanation for the gap. Our research provides evidence that employers use information on employment gaps as additional signals about workers' unobserved productivity. Co-authored with Dr. Amanda Gaulke and Dr. Hugh Cassidy, the second essay tests how employers perceive the value of post-baccalaureate certificates using the same methodology in the first essay. We randomly assign a post-baccalaureate certificate credential to fictitious résumés and apply to real vacancy postings for managerial, administrative and accounting assistant positions on a large online job board. We find that post-baccalaureate certificates are 2.4 percentage points less likely to receive a callback than those without this credential. However, this result is driven by San Francisco, and there is no effect in Los Angeles or New York. By occupation, we also find that there is only significant negative effect in administrative assistant jobs, and there is none in managerial or accounting assistant jobs. A typographical error made in the résumés of certificate holders regarding the expected year of completion of the certificate may also contribute to negative effects of a certificate. Using NLSY79 data, the third essay tests whether the source of health insurance creates incentives for newly-diagnosed workers to remain sufficiently employed to maintain access to health insurance coverage. I compare labor supply responses to new diagnoses of workers dependent on their own employment for health insurance with the responses of workers who are dependent on their spouse's employer for health insurance coverage. I find that workers who depend on their own job for health insurance are 1.5-5.5 percentage points more likely to remain employed and for those employed, are 1.3-5.4 percentage points less likely to reduce their labor hours and are 2.1-6.1 percentage points more likely to remain full-time workers.
Keywords: Correspondence study; Employer-sponsored health insurance; Labor supply; Labor demand; Post-baccalaureate certificate